2019
DOI: 10.1103/physrevresearch.1.033036
|View full text |Cite
|
Sign up to set email alerts
|

Photonic quantum walks with four-dimensional coins

Abstract: The dimensionality of the internal coin space of discrete-time quantum walks has a strong impact on the complexity and richness of the dynamics of quantum walkers. While two-dimensional coin operators are sufficient to define a certain range of dynamics on complex graphs, higher-dimensional coins are necessary to unleash the full potential of discrete-time quantum walks. In this work, we present an experimental realization of a discrete-time quantum walk on a line graph that, instead of two-dimensional, exhibi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…While implementing a time-domain reconfigurable loop architecture as described above is not a straightforward task, several groups have performed experiments with tens of modes interfering in time-domain multiplexed configurations. These include time-bin ( 35 ) and temporal-to-spatial–encoded ( 36 ) boson sampling experiments ( 35 ) and controllable photonic random walk over multiple time-bins ( 37 , 38 ). Moreover, recent experiments have shown that it is possible to operate with very high phase stability ( 39 ), high quantum-efficiency photon-number detection ( 40 ), and very low loss reconfigurable interferometric elements ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…While implementing a time-domain reconfigurable loop architecture as described above is not a straightforward task, several groups have performed experiments with tens of modes interfering in time-domain multiplexed configurations. These include time-bin ( 35 ) and temporal-to-spatial–encoded ( 36 ) boson sampling experiments ( 35 ) and controllable photonic random walk over multiple time-bins ( 37 , 38 ). Moreover, recent experiments have shown that it is possible to operate with very high phase stability ( 39 ), high quantum-efficiency photon-number detection ( 40 ), and very low loss reconfigurable interferometric elements ( 41 ).…”
Section: Resultsmentioning
confidence: 99%
“…This result alone could play an important role e.g. in experimental scenarios like [8] which are by construction limited to a one-dimensional walking space but have a higher than two-dimensional coin space. Equation (27) shows that the various phases ϕ could be accessed by varying a phase parameter in the step operator, which could perhaps be achieved directly by means of sub-wavelength optical pulse dilations.…”
Section: Applicationsmentioning
confidence: 96%
“…With a special case of k = 1, we obtain a walk on a line with doubled edges. This is an interesting scenario because it is one the dynamics of which are explored experimentally in [8].…”
Section: Projection Theorymentioning
confidence: 99%
“…universal quantum simulator [72][73][74][75][76]. We devised a looped Michelson interferometer as a platform for time-multiplexed quantum walks, which overcomes some of the restrictions of previous implementations [77]. The main advantage of this architecture is a higher dimensional internal state for walkers (i.e., the photons), arising from the additionally available traveling direction in the loop, clockwise and counter-clockwise.…”
Section: A Motivation and Setup Descriptionmentioning
confidence: 99%
“…In addition, we successfully implemented three electro-optic modulators (EOMs) in our setup to manipulate the polarization of the travelling photons. This increased configurability allowed us to study the walker's evolution on complex graph structures, such as realizing quantum walks on a circle with periodic boundary conditions and other scenarios which are only accessible with higher dimensional internal states [77].…”
Section: A Motivation and Setup Descriptionmentioning
confidence: 99%